Surfactants and interfacial phenomena - Rosen, Milton J.; Kunjappu, Joy T. (Hoboken, N.J. : John Wiley & Sons, 2012)
'This book provides an easy-to-read, user-friendly resource for industrial chemists and a text for classroom use, and is an unparalleled tool for understanding and applying the latest information on surfactants. Problems are included at the end of each chapter to enhance the reader's understanding, along with many tables of data that are not compiled elsewhere. Only the minimum mathematics is used in the explanation of topics to make it easy-to-understand and very user friendly'--
Includes index.
Keywords: Surface active agents; Surface chemistry